NS Segment of a 1918 Influenza A Virus-Descendent Enhances Replication of H1N1pdm09 and Virus-Induced Cellular Immune Response in Mammalian and Avian Systems - Petersen, Henning; Mostafa, Ahmed; Tantawy, Mohamed A.; Iqbal, Azeem A.; Hoffmann, Donata; Tallam, Aravind; Selvakumar, Balachandar; Pessler, Frank; Beer, Martin; Rautenschlein, Silke; Pleschka, Stephan (Frontiers in Microbiology, 2018)
The 2009 pandemic influenza A virus (IAV) H1N1 strain (H1N1pdm09) has widely spread and is circulating in humans and swine together with other human and avian IAVs. This fact raises the concern that reassortment between H1N1pdm09 and co-circulating viruses might lead to an increase of H1N1pdm09 pathogenicity in different susceptible host species. Herein, we explored the potential of different NS segments to enhance the replication dynamics, pathogenicity and host range of H1N1pdm09 strain A/Giessen/06/09 (Gi-wt). The NS segments were derived from (i) human H1N1- and H3N2 IAVs, (ii) highly pathogenic- (H5- or H7-subtypes) or (iii) low pathogenic avian influenza viruses (H7- or H9-subtypes). A significant increase of growth kinetics in A549 (human lung epithelia) and NPTr (porcine tracheal epithelia) cells was only noticed in vitro for the reassortant Gi-NS-PR8 carrying the NS segment of the 1918-descendent A/Puerto Rico/8/34 (PR8-wt, H1N1), whereas all other reassortants showed either reduced or comparable replication efficiencies. Analysis using ex vivo tracheal organ cultures of turkeys (TOC-Tu), a species susceptible to IAV H1N1 infection, demonstrated increased replication of Gi-NS-PR8 compared to Gi-wt. Also, Gi-NS-PR8 induced a markedly higher expression of immunoregulatory and pro-inflammatory cytokines, chemokines and interferon-stimulated genes in A549 cells, THP-1-derived macrophages (dHTP) and TOC-Tu. In vivo, Gi-NS-PR8 induced an earlier onset of mortality than Gi-wt in mice, whereas, six-week-old chickens were found to be resistant to both viruses. These data suggest that the specific characteristics of the PR8 NS segments can impact on replication, virus induced cellular immune responses and pathogenicity of the H1N1pdm09 in different avian and mammalian host species.